A SECOND SPECIMEN OF THE ARCHAIC MEDITERRANEAN MONODONTID CETACEAN CASATIA THERMOPHILA FROM THE ZANCLEAN DEPOSITS OF ARCILLE (TUSCANY, ITALY) - Marco MERELLA; Alberto COLLARETA; Valerio GRANATA; Simone CASATI; Giovanni BIANUCCI (Alma Mater Studiorum - Università di Bologna, 2021)
The white whale Delphinapterus leucas (also known as the beluga) and the narwhal Monodon monoceros are the only extant members of the family Monodontidae (Cetacea, Odontoceti, Delphinoidea). These two species are exclusive of Arctic and subarctic cold waters. They are well known as iconic cetaceans by virtue of a white skin color (in case of D. leucas) and a spiraled tusk (in case of M. monoceros). Differing from other groups of odontocetes cetaceans, the monodontids are known as fossils from just a handful of specimens. Only four species have been described in literature, all being known by the sole holotype, namely: Bohaskaia monodontoides, Denebola brachycephala, Haborodelphis japonicus and Casatia thermophila. In particular, C. thermophila is the only fossil monodontid to have ever been found in the whole Mediterranean basin. Here we describe a second specimen of C. thermophila, from its lower Pliocene type locality of Arcille (Grosseto Province, Tuscany, central Italy). The new find consists of three cervicals (including the axis) and two lumbars. This fossil resembles the holotype in terms of overall size and cranial morphology, and especially, by displaying a similarly depressed portion of the dorsal surface of the premaxillae anterior to the premaxillary sac fossae and medial to the anteromedial sulci. Our new find is thus assigned to C. thermophila, and significant anatomical parts that are missing in the holotype are described in order to improve the diagnosis of this monodontid species. Several dentigerous fragments of the maxillae hint at a homodont and polydont dentition, which in turn suggests a ram prey capture method that differs from the highly derived suction method that is proper of extant monodontids. This second specimen of C. thermophila from the warm-water Arcille palaeoenvironment lends further support to the hypothesis that monodontids once thrived in tropical and subtropical habitats.